Evidence of central sensitisation in those with dry eye symptoms and neuropathic-like ocular pain complaints: incomplete response to topical anaesthesia and generalised heightened sensitivity to evoked pain. Issue 9 (18th January 2017) - Crane, Ashley M; Feuer, William; Felix, Elizabeth R; Levitt, Roy C; McClellan, Allison L; Sarantopoulos, Konstantinos D; Galor, Anat
Abstract : Objective: To evaluate how closely neuropathic-like ocular pain (NOP) symptoms align with a metric of central sensitisation (ie, the presence of persistent ocular pain after topical anaesthetic placement) in individuals with dry eye (DE) symptoms. Design: Cross-sectional study of 224 individuals with DE symptoms seen in the Miami Veterans Affairs eye clinic. An evaluation was performed consisting of questionnaires regarding DE symptoms, NOP descriptors and evoked pain sensitivity testing on the forehead and forearm, followed by a comprehensive ocular surface examination including corneal mechanical sensitivity testing. Subsequent analyses were performed to examine for differences between those with and without ocular pain after topical anaesthetic placement. Results: The mean age was 62 years with 91% being men. DE symptoms and NOP symptoms were higher in subjects with persistent ocular pain after anaesthesia. Most DE signs were not related to persistent pain, with the exception of meibum quality. Individuals with persistent ocular pain also demonstrated greater sensitivity to evoked pain at testing sites on the forehead and forearm. When examining receiver operator characteristic curves considering persistent pain as a gold standard for central sensitisation within the corneal pathway, intensity of ocular pain ratings, Ocular Surface Disease Index scores and sensitivity to light provided the most robust relationships, each with an area under the curve of 0.72. Conclusions: Individuals with DE symptoms and persistent ocular pain after topical proparacaine (a marker of central sensitisation to pain) more frequently report NOP-like symptoms and demonstrate increased sensitivity to evoked pain.